Accuracy of Uterine Artery Doppler in Second Trimester in Determining Pre-Eclampsia - Amna Khalid , Misbah Durrani , Khola Riaz , Muhammad Waqas , Fazal Husain Shah , Lubna Farooq (Journal of Rawalpindi Medical College, 2018)
Background: To determine the accuracy of uterine artery doppler in the second trimester (18-24 weeks) in determining preeclampsia. Methods: In this descriptive study, a total of 89 women with singleton pregnancy attending routine second-trimester anomaly scan were included. Uterine artery doppler sonography was conducted in the women coming for routine anomaly scan. Flow velocity waveforms of right and left uterine artery were imaged with the patient in the semi-recumbent position and the uterine artery was identified in the longitudinal scan, lateral to the uterus. Resistive index, pulsatility index and presence and absence of early diastolic notch and its depth in terms of notch index were calculated. Results: Uterine artery doppler finding in second trimester in determining preeclampsia showed abnormal findings in 41.57% women in which 24.32% had type I (Resistive index >0.58), 45.95% (17/37) type II (Mild notching of uterine artery at beginning of diastole) and 29.73% had type III [(Severe notching + abnormal Resistive index (>0.58)]. After the follow-up of each patient, we found that pre-eclampsia was developed in 28.09% (25/89) cases. The accuracy, sensitivity, specificity, positive and negative predictive values of uterine artery doppler were 75.28%, 80%, 73.44%, 54.05% and 90.38% respectively Conclusion: By detecting abnormal uterine artery Doppler indices (high RI) between 18-24 weeks of pregnancy can identify those women who are at risk for development of preeclampsia.